History Of Rubobs - Umarov Muhammadjon Xurboyevich (Peerian Journals Publishing, 2022)
Information about the word rubab, its origin, structure, setting, types and current significance
Keywords: Abu Nasr Faroobi; Najmiddin Kavkabi; Darvish Ali Changhi; Kashgar rubab